Model‐Based Prediction of Irinotecan‐Induced Grade 4 Neutropenia in Advanced Cancer Patients: Influence of Demographic and Clinical Factors. Issue 2 (18th May 2022) - Karas, Spinel; Mathijssen, Ron H. J.; van Schaik, Ron H. N.; Forrest, Alan; Wiltshire, Tim; Innocenti, Federico; Bies, Robert R.
Abstract : Severe neutropenia is the major dose‐liming toxicity of irinotecan‐based chemotherapy. The objective was to assess to what extent a population pharmacokinetic/pharmacodynamic model including patient‐specific demographic/clinical characteristics, individual pharmacokinetics, and absolute neutrophil counts (ANCs) can predict irinotecan‐induced grade 4 neutropenia. A semimechanistic population pharmacokinetic/pharmacodynamic model was developed to describe neutrophil response over time in 197 patients with cancer receiving irinotecan. For covariate analysis, sex, race, age, pretreatment total bilirubin, and body surface area were evaluated to identify significant covariates on system‐related parameters (mean transit time (MTT) and ɣ) and sensitivity to neutropenia effects of irinotecan and SN‐38 (SLOPE). The model‐based simulation was performed to assess the contribution of the identified covariates, individual pharmacokinetics, and baseline ANC alone or with incremental addition of weekly ANC up to 3 weeks on predicting irinotecan‐induced grade 4 neutropenia. The time course of neutrophil response was described using the model assuming that irinotecan and SN‐38 have toxic effects on bone marrow proliferating cells. Sex and pretreatment total bilirubin explained 10.5% of interindividual variability in MTT. No covariates were identified for SLOPE and γ. Incorporating sex and pretreatment total bilirubin (area under the receiver operating characteristic curve (AUC‐ROC): 50%, 95% CI 50–50%) or with the addition of individual pharmacokinetics (AUC‐ROC: 62%, 95% CI 53–71%) in the model did not result in accurate prediction of grade 4 neutropenia. However, incorporating ANC only at baseline and week 1 in the model achieved a good prediction (AUC‐ROC: 78%, 95% CI 69–88%). These results demonstrate the potential applicability of a model‐based approach to predict irinotecan‐induced neutropenia, which ultimately allows for personalized intervention to maximize treatment outcomes.